Phytochemical, antioxidant and cytotoxicity studies of Bambusa arundinacea leaves - Shaukat Hussain Naz,; Muhammad Zubair,; Komal Rizwan,; Nasır Rasool,; Iftikhar Hussain Bukhari,; Muhammad Jamil,; Muhammad Riaz,; Muhammad Imran,; Mazhar Abbas, (International Journal of Phytomedicine, 2012)
Medicinal plants, as a source of remedies, are widely used as alternative therapeutic utensils for the anticipation or treatment of many diseases. The Present study was carried out to investigate the medicinal importance of the plant Bambusa arundinacea leaves. The various extracts obtained from the plant leaves were analyzed for their phytochemical constituents, in vitro antioxidant, haemolytic acivities and stability of corn oil. The plant leaves contained appreciable levels of total phenolic contents (3.7-12.71 GAE mg/g of dry extract) and total flavonoid contents (2.31-6.71 CE mg/g of dry extract). DPPH radical scavenging (IC50) and percentage inhibition of linoleic acid peroxidation was found to be in the range of 278-1536 μg/mL and 24.41-78.05% respectively. The antioxidant activity of plant extracts was also studied using corn oil as an oxidative substrate and found that it stabilized the oil. The haemolytic effect of the plant leaves was found in range of 0.70-2.88%. The results of the present investigation demonstrated significant (p < 0.05) variations. The correlation between the results of different antioxidant assays and oxidation parameters of oil indicated that plant leaves to be a potent source of antioxidants for stabilization of corn oil